Cost‐of‐illness of patients with lymphoedema. (10th October 2017) - Gutknecht, M.; Herberger, K.; Klose, K.; Purwins, S.; Dietz, D.; Blome, C.; Augustin, M.
Abstract: Background: Chronic lymphoedema is characterized by a continuous need for medical treatment, many comorbidities and impaired quality of life. In Germany, about 4.5 million patients are affected by lymphoedema. Thus, lymphoedema causes high direct and indirect costs, even more in case of complications such as erysipelas and ulcers. Objective: The aim of this study was to determine the costs of illness of community lymphoedema patients living in the metropolitan area of Hamburg, Germany. Methods: An observational cross‐sectional study in patients with lymphoedema and combined lipolymphoedema of any origin was performed analysing direct and indirect costs for the patients, the statutory health insurance and society. Results: In total, 348 patients (90.8% female) were examined and interviewed. The mean age of the patients was 57.3 ± 14.5 years. On average, the total costs per patient and year were € 5784, of which € 4445 (76.9%) were direct costs and € 1338 indirect costs. Within the direct medical costs, € 3796 were accounted for the statutory health insurances and € 649 for the patient. The main cost drivers were costs for manual decongestive therapy and disability costs. Conclusion: Chronic lymphoedema is associated with high direct and indirect costs. This community‐based study is the first cost analysis of chronic lymphoedema and combined lipolymphoedema giving insights to economic impact of lymphoedema treatment. There is a high need for structured disease management programs in order to diagnose and treat lymphoedema early and to avoid complications, thus limiting socio‐economic burden.